Recent Trends and Overall Survival of Young Versus Older Adults With Stage II to III Rectal Cancer Treated With and Without Surgery in the United States, 2010-2015. (October 2020) - Sanford, Nina N.; Dee, Edward C.; Ahn, Chul; Kazmi, Syed A.; Beg, Muhammad S.; Folkert, Michael R.; Aguilera, Todd A.; Polanco, Patricio M.; Pogacnik, Javier S.; Sher, David J.
Abstract : Background: The omission of surgery via nonoperative management (NOM) for rectal cancer may be increasing, and this strategy could be particularly attractive for younger patients, whose incidence of rectal cancer has been rising. We sought to assess trends in NOM in young (younger than 55 y) versus older adult (55 y and older) rectal cancer cohorts. Methods: The National Cancer Database was used to identify patients diagnosed with stage II to III rectal cancer between 2010 and 2015. Multivariable logistic regression defined the association between sociodemographic variables and odds of NOM, including an age (18 to 54 vs. 55+ y)×surgery (surgery vs. NOM) interaction term. Adjusted Cox regression models compared overall survival between NOM versus surgery. Results: Among 22, 561 patients with a median follow-up of 37.5 months, the utilization rate of NOM increased from 10.7% (2010) to 15.2% (2015). Older patients were more likely to receive NOM, although rates also increased among young (7.1% to 10.6%). Black patients were also more likely to receive NOM ( P <0.001). Among the entire cohort, NOM was associated with worse overall survival (adjusted hazard ratio [AHR]=2.90, 95% confidence interval [CI]: 2.67-3.15) and there was a statistically significant age×NOM interaction ( P =0.01) such that the effect of NOM on survival was worse for younger (AHR=3.37, 95% CI: 2.82-4.02) as compared with older patients (AHR=2.49, 95% CI: 2.27-2.74). Conclusions: The increasing trend for NOM in stage II to III rectal cancer may be driven by disparities in treatment. Management with NOM appears to be associated with poorer survival, particularly in younger patients and could worsen outcomes for groups already at risk for suboptimal cancer care.